Effect of TGFβ1, TGFβ3 and keratinocyte conditioned media on functional characteristics of dermal fibroblasts derived from reparative (Balb/c) and regenerative (Foxn1 deficient; nude) mouse models - Bukowska, Joanna (Cell Tissue Res, 2018)
Skin injuries in mammals are healed through repair or regeneration. Our previous studies demonstrated that deficient expression of the transcription factor Foxn1 in epidermis of nude mice accounts for their skin’s pronounced regenerative properties. Since homeostasis within the skin depends on complex interactions between the epidermal and underlying dermal layers, the present study characterizes and compares isolated dermal fibroblasts (DFs) between regenerative nude (Foxn1 deficient) mice and their wild-type Balb/c counterparts. Nude DFs exhibited a higher cumulative number of population doublings (cumulative PD) at low seeding density and increased adipogenic differentiation capacity relative to their Balb/c DF counterparts. Nude DFs displayed reduced migration and gel contraction, functional features associated with wound healing. The comparison of transforming growth factor β family (TGFβ) expression showed significantly higher levels of Tgfβ3 transcript between nude and Balb/c mice but no differences were detected for Tgfβ1. Nude DFs were specifically sensitive to the presence of the pro-regenerative TGFβ3 isoform, showing increased collagen I deposition and alpha smooth muscle actin expression. Viability of Balb/c DFs was stimulated by keratinocyte conditioned media (KCM) from Balb/c (Foxn1 active) but inhibited by nude (Foxn1 deficient) KCM. In contrast, nude DFs did not respond to either KCMs with respect to their metabolic activity. Collectively, the enhanced plasticity and greater sensitivity of nude DFs to TGFβ3 stimulation are indicative of and consistent with their pro-regenerative characteristics. These data support the hypothesis that epidermal Foxn1 plays a critical role in determining the DFs regenerative phenotype.